Serum leptin, a potential predictor of long‐term angiographic progression in Takayasu's arteritis. (9th October 2019) - Ma, Lili; Yu, Wensu; Dai, Xiaomin; Yin, Mengmeng; Wang, Yujiao; Sun, Ying; Kong, Xiufang; Cui, Xiaomeng; Wu, Sifan; Ji, Zongfei; Ma, Lingying; Chen, Huiyong; et al.
Abstract: Aim: In patients with Takayasu's arteritis (TA), current biomarkers that properly reflect the progression of the vascular structure remain absent. We aimed to determine the serum leptin level to investigate its relationship with imaging changes and assess its value as a predictor for long‐term radiological progression. Method: This study included 34 untreated TA patients and 40 age‐matched healthy controls. At baseline and during the 5‐year follow‐up, we assessed disease activity using Kerr's criteria and Indian Takayasu Clinical Activity Score (ITAS2010) and monitored laboratory biomarkers as well as imaging findings. Serum leptin levels were measured by enzyme‐linked immunosorbent assay. Results: The baseline serum leptin levels were significantly higher in TA patients than in healthy controls. Leptin was significantly positively correlated with triglyceride and high‐density lipoprotein cholesterol levels and negatively correlated with fibrinogen and C‐reactive protein levels. Patients were subdivided into three groups based on their baseline leptin level. During a 5‐year follow‐up, patients in the high and medium leptin groups showed more radiological progression compared to those in the low leptin group. Cox proportional hazard regression analysis showed that a high serum leptin level was a positive predictor of radiological progression. Conclusion: Leptin is a potential biomarker for assessing TA structural progression. Untreated patients with elevated serum leptin levels are at a higher risk of progression in the aorta. Thus, the leptin level can be a predictor of long‐term radiological progression.